PENENTUAN CABANG USAHATANI PADI, JAGUNG, DAN KEDELAI YANG OPTIMUM MELALUI POLA DIVERSIFIKASI DENGAN PENDEKATAN LINEAR PROGRAMMING DI KABUPATEN MUARO JAMBI - Yusma Damayanti; Riri Oktari Ulma (Universitas Sebelas Maret, 2019)
This study aims to: (1) establish an approach to determine the optimum scale of rice, corn, and soybean that can be managed by farmers according to their limitations, (2) to find out whether rice, corn, and soybean that optimum are cultivated by farmers, (2) to know and analyze cropping pattern that provide maximum income. This research was conducted in Petanang and Sungai Aur Village, Kumpeh District, Muaro Jambi Regency. The sample farmers in this research are 56 farmers who do farming with pajale system (rice, corn, and soybean). The analytical method used is descriptive and quantitative analysis. The results showed that there were 3 cropping patterns that had the potential to be optimized, namely pattern 1: potential rice, maize and soybeans to be cultivated in MT I, MT II, and MT III of the available land area with a 300% cropping index covering 4.8 ha, pattern II; rice is cultivated in MT I with a maximum area of 1.6 ha. Whereas potential maize and soybeans are cultivated in MT II and III of the available land area with a 200% cropping index covering 3.2 ha. - Cropping pattern III; rice is cultivated only in MT I, maize in MT II and soybeans in MT III, with a maximum area of 1.6 ha. Rice and corn commodities are considered optimal for development by farmers in the study area. Of the three cropping patterns the most optimal is the cropping pattern I, followed by cropping patterns of models II and III.